New 4(3) Pairs Diagonally Implicit Runge-Kutta-Nyström Method for Periodic IVPs - Norazak Senu; Mohamed Suleiman; Fudziah Ismail; Norihan Md Arifin (Discrete Dynamics in Nature and Society)
New 4(3) pairs Diagonally Implicit Runge-Kutta-Nyström (DIRKN) methods with reduced phase-lag are developed for the integration of initial value problems for second-order ordinary differential equations possessing oscillating solutions. Two DIRKN pairs which are three- and four-stage with high order of dispersion embedded with the third-order formula for the estimation of the local truncation error. These new methods are more efficient when compared with current methods of similar type and with the L-stable Runge-Kutta pair derived by Butcher and Chen (2000) for the numerical integration of second-order differential equations with periodic solutions.